Renal Stent Migration Following TEVAR for Complicated Type B Aortic Dissection. (July 2019) - Iwakoshi, Shinichi; Sakaguchi, Shoji; Kakii, Bunpachi; Yoshida, Takeshi; Watkins, Amelia Claire; Inoue, Takeshi; Ichihashi, Shigeo; Kichikawa, Kimihiko
We describe renal stent migration following thoracic endovascular aortic repair (TEVAR) for type B aortic dissection. A 68-year-old male presented with type B aortic dissection. His course was complicated by renal and lower extremity malperfusion. Thoracic endovascular aortic repair was performed and completion angiogram showed no flow in the left renal artery. A renal stent was deployed with the proximal margin of the stent 1 mm into the aortic true lumen, providing improved renal perfusion. One week after TEVAR, contrast-enhanced computed tomography (CT) revealed that the renal stent had embolized to the aortic bifurcation. Additional endovascular therapy successfully crushed the renal stent against the iliac artery wall utilizing a larger bare metal stent. At 3 year follow-up, contrast-enhanced CT demonstrated good patency of the left renal artery and right iliac artery. This complication alerts physicians to consider subsequent aortic remodeling during endovascular intervention for acute aortic dissection with malperfusion.